The Private Military Company Complex in Central and Southern Africa: The Problematic Application of International Humanitarian Law - Mathew Kincade III (Washington University Global Studies Law Review, 2013)
The presence of Private Military Companies (“PMCs”) in contemporary warfare represents a remarkable transition from warfare practices prior to the Cold War. Instead of traditional overt and direct opposition between countries or superpowers, PMCs act as “private providers” of physical protection or armed force for their clients. A PMC is a private corporation that specializes in security or armed force. Like any corporation that resides in a particular nation, a PMC must abide by the laws of a particular sovereign. However, given that PMCs often contract with countries that face both internal and external conflicts (potentially involving other nations), the threat of international conflict remains a pressing concern. Since human rights violations are always a concern during international warfare, International Humanitarian Laws (“IHLs”) aim to control state armies and ensure basic protections of human rights in armed conflict. There is some debate, however, as to whether or not IHLs apply to PMCs in the same fashion they can at times apply to sovereigns. IHLs do not explicitly refer to PMCs, and most attempts to retroactively fit PMCs into IHL interpretations have been problematic. International legislation is also partially responsible for the difficulties in applying IHLs to PMCs due to the combination of a lack of time, effort, and political motivation for some sovereigns to address the issues. As a result, PMC activities potentially fall into a troublesome gray area with respect to human rights protections in armed conflict.
Keywords: private military companies; international humanitarian law; Africa